Pembakaran Mushaf Al-Qur’an Yang Rusak Dalam Tradisi Masyarakat Muslim: Sebuah Transmisi Dan Transformasi - Nafisatul Mu'awwanah (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2018)
This article tries to explain how the phenomenon of combustion copy of the Qur’an were damaged in the tradition of Muslim societies occur. Muslim society in everyday life, when see copy of the Koran that have been damaged or torn Koran, one of them is to burn reception. Combustion also applies to writings containing God asthma or other materials which are writings of the Koran, such as magazines, pamphlets, tabloids, and so forth. This phenomenon is seen through the perspective of reception theory, which says that each side pratek Muslims emerged from the theological side, which in this case is the belief that the Qur’an is the word of God. The phenomenon discovered in the transmission and transformation in peresepsiannya process. The reception transmission copy of the Koran burning damaged were of literature-literature jurisprudence and adab al-Qur'an, which further transmission to the copy of the Koran burning in the reign of Ustman ibn ‘Affan. The transformation of this peresepsian process is related to the background and purpose of combustion, as well as the object or material is burned.